2016
DOI: 10.1007/s11325-016-1426-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of drug-induced sedation endoscopy: interobserver agreement

Abstract: Overall, DISE is a reliable technique even when assessing interobserver agreement between an experienced observer and one in training; however, tongue base is the level of the upper airway that presents the greatest difficulties when assessing the collapse with DISE. Therefore, it is important to develop learning curves for this technique in order to obtain more reliable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
1
41
0
3
Order By: Relevance
“…In this report the VOTE classification correlated with OSA severity and identified a number of affected sites; this study anesthetic level was described with bispectral assessments (BIS) 39 . In the use of VOTE in a DISE setting, the interobserver agreement between an experienced observer and a learner does have a learning curve, but the problem area is more often at the tongue base, rather than the velopharynx or the epiglottis 40 . The DISE can be used for planning other treatments that might be offered to CPAP-intolerant patients 41 .…”
Section: The Vote Classificationmentioning
confidence: 99%
“…In this report the VOTE classification correlated with OSA severity and identified a number of affected sites; this study anesthetic level was described with bispectral assessments (BIS) 39 . In the use of VOTE in a DISE setting, the interobserver agreement between an experienced observer and a learner does have a learning curve, but the problem area is more often at the tongue base, rather than the velopharynx or the epiglottis 40 . The DISE can be used for planning other treatments that might be offered to CPAP-intolerant patients 41 .…”
Section: The Vote Classificationmentioning
confidence: 99%
“…) showed that the rate of a closure of 75% or more at the level of the soft palate was 69.3% (95% CI: 48.3%–79.6%). A total of 210 patients from five studies were included in the meta‐analysis of the degree of closure at the level of the hypopharynx . Because heterogeneity was not present among the studies, a fixed‐effects model was used.…”
Section: Resultsmentioning
confidence: 99%
“…In the electronic databases, we entered keywords in the following combination: "obstructive sleep apnea," "sleep apnea," or "OSA"; and "sleep endoscopy," "drug induced sleep endoscopy," or "DISE." [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In addition, we examined the references of three review articles related to DISE. 31,32 The search was performed on November 13, 2017.…”
Section: Literature Sources and Study Identificationmentioning
confidence: 99%
See 2 more Smart Citations